Faces of Resistance : Maya Heroes, Power, and Identity - Kistler, S. Ashley, 1978- (Book collections on Project MUSE., 2018)
"The Maya have faced innumerable and constant challenges to their cultural identities in the last 500 years, from the subjugation of the contact and colonial periods, to the brutality of state-sponsored violence in Guatemala and the introduction of new global technologies. Oral tradition plays a fundamental role among the contemporary Maya as a means to record history and resist oppression. Although scholars have examined the processes of resistance and identity in different spheres, The Faces of Resistance: Maya Heroes, Power, and Identity is the first to unpack the importance of heroes as a cornerstone of Maya cultural and political resistance. This collection of essays by leading scholars explores how Maya communities draw on stories of indigenous heroes as an empowering cultural memory and a way to connect with the legacy of their extraordinary past. In particular, this volume considers how the Maya, following centuries of persecution and marginalization, use historical knowledge to generate and fortify their indigenous identities. The analysis of Maya heroes presented in this volume reveals that narratives of hero figures help the Maya to re-connect with an understanding of their history that has survived centuries of oppression and legitimize the practices, beliefs, and morality that will define their future"--